Quality of antenatal and childbirth care in rural health facilities in Burkina Faso, Ghana and Tanzania: an intervention study - Duysburgh, Els; Temmerman, Marleen; Yé, Maurice; Williams, Afua; Massawe, Siriel; Williams, John; Mpembeni, Rose; Loukanova, Svetla; Haefeli, Walter E.; Blank, Antje (Tropical medicine & international health, 2016)
Objective To assess the impact of an intervention consisting of a computer-assisted clinical decision support system and performance-based incentives, aiming at improving quality of antenatal and childbirth care. Methods Intervention study in rural primary healthcare (PHC) facilities in Burkina Faso, Ghana and Tanzania. In each country, six intervention and six non-intervention PHC facilities, located in one intervention and one non-intervention rural districts, were selected. Quality was assessed in each facility by health facility surveys, direct observation of antenatal and childbirth care, exit interviews, and reviews of patient records and maternal and child health registers. Findings of pre- and post-intervention and of intervention and non-intervention health facility quality assessments were analysed and assessed for significant (P < 0.05) quality of care differences. Results Post-intervention quality scores do not show a clear difference to pre-intervention scores and scores at non-intervention facilities. Only a few variables had a statistically significant better post-intervention quality score and when this is the case this is mostly observed in only one study-arm, being pre-/post-intervention or intervention/non-intervention. Post-intervention care shows similar deficiencies in quality of antenatal and childbirth care and in detection, prevention, and management of obstetric complications as at baseline and non-intervention study facilities. Conclusion Our intervention study did not show a significant improvement in quality of care during the study period. However, the use of new technology seems acceptable and feasible in rural PHC facilities in resource-constrained settings, creating the opportunity to use this technology to improve quality of care.
First published: 26 October 2015
Gesehen am 29.04.2020